Ali Cross : like father, like son - Patterson, James, 1947-; OverDrive, Inc. (New York : Jimmy Patterson Books/Little, Brown and Company, 2021)
Ali Cross is back in the gripping sequel to Ali Cross, the best-selling mystery that introduced readers to detective Alex Cross' son. In Ali's toughest case ever, his friend Zoe is in trouble after Ali and his friends witnessed a crime in Anacostia Park, and it's up to Ali to figure out why Zoe is lying to the police--and who she's protecting.
Electronic book.
Ages 10-14.
Accelerated Reader AR
Electronic reproduction.
Keywords: Advantage title -- Fiction; Child detectives -- Juvenile fiction; Child witnesses -- Juvenile fiction; Middle school students -- Juvenile fiction; Criminal investigation -- Juvenile fiction; Witnesses -- Juvenile fiction; Friendship -- Juvenile fiction; Truthfulness and falsehood -- Juvenile fiction; Child detectives -- Fiction; Witnesses -- Fiction; Mystery and detective stories; JUVENILE FICTION / Mysteries & Detective Stories; Child detectives; Friendship; Middle school students; Truthfulness and falsehood; Witnesses; Washington (D.C.) -- Juvenile fiction; Washington (D.C.); Detective and mystery fiction; Fiction; Juvenile works; Mystery fiction; Detective and mystery fiction; Electronic books; Detective fiction; Mystery fiction